Massive collision tumor of ovary in pregnancy: rare successful perinatal outcome - Anant, Monika; Sharma, Mrinal; Bharti, Shreekant; Paswan, Anita; Pritam, Anuja; Raj, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
A collision tumor is the co-existence of two adjoining but histologically distinct tumors without histological admixture in the same tissue or organ. The most common histological combination of collision tumor in the ovary is the coexistence of mature teratoma with mucinous cystadenomas. The incidence of adnexal mass in pregnancy is 0.05-2.4% of which 94-99% are benign. The 1-6% maybe malignant requiring more extensive surgical procedures that increases likelihood of pregnancy loss. Ovarian tumors first diagnosed during pregnancy often present a challenge for diagnosis and management. Hence accurate knowledge of tumor characteristics, especially the ultrasound appearance and gestational age at diagnosis, are the key prerequisites for establishing the most effective plan of management for the pregnant women. To the best of our knowledge this report of huge collision tumor with successful pregnancy outcome is first of its kind.